Food values and purchase decisions in emerging markets: Empirical evidence from Kenya - Opeyemi Femi-Oladunni; Pablo Ruiz-Palomino; Maria Pilar Martinez-Ruiz; Israel Roberto Perez-Jimenez (Cogent Business & Management, 2023)
Research on consumer food value preferences has typically focused on consumers in the developed economy, with knowledge regarding food value preferences in emerging food markets being a grey spot. This study aims to fill this gap in the literature. Accordingly, the possible existence of consumer clusters in Kenya based on their appreciation of food values is analyzed. The differences in the appreciation of food values were studied considering the socio-demographic traits of 500 random consumers, for which a standardized questionnaire was used. In the empirical analysis, Spearman's correlation test, two-step cluster analyses and logistic regressions were calculated. The results reveal variations in food value preferences between segments determined by economic and socio-environmental factors. Nutrition was the most preferred value, while environmental impact was the least preferred.
Keywords: 650; cluster analysis; food values; multivariate logistic regression; sociodemographic characteristics; Sub-Saharan Africa